Effectiveness of underpass advertising in Singapore : an exploratory study. - Ong, Cindy Yen Peng. (2008)
This paper focuses on attesting the effectiveness of underpass advertising in Singapore, particularly within the Orchard underpass, with a comparison of advertisements placed in scrolling panels versus stationary ones.